1958
DOI: 10.1111/j.2044-8295.1958.tb00650.x
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and Social Changes in the Feebleminded—three Further Studies

Abstract: Earlier papers have described researches showing that i.q. increments in adolescent and young adult persons certified as feebleminded occur not infrequently, cannot be explained as artefacts, and appear to be linked with early very adverse environmental experiences. The present three studies indicate that i.q. increments can be large over long periods of time, are correlated with changes in social adjustment, but cannot be shown to be induced by special environmental stimulation; in the present age range and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

1970
1970
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(33 citation statements)
references
References 5 publications
2
31
0
Order By: Relevance
“…The migration of the term resilience from mechanics, manufacturing and medicine to the social sciences began in a small way the 1950s (Clarke et al, 1958). The use of the term "resilience" in the developmental psychopathology of children owes much to the work of the American psychiatrist Norman Garmezy (1918Garmezy ( -2009.…”
Section: Social Sciencesmentioning
confidence: 99%
“…The migration of the term resilience from mechanics, manufacturing and medicine to the social sciences began in a small way the 1950s (Clarke et al, 1958). The use of the term "resilience" in the developmental psychopathology of children owes much to the work of the American psychiatrist Norman Garmezy (1918Garmezy ( -2009.…”
Section: Social Sciencesmentioning
confidence: 99%
“…For example, a child from a disorganized or depriving home would find the institution a relatively stimulating place by comparison (2). In the present study IQ changes in the Institutional Sample did not relate to the families' initial overall level of functioning nor to their change in functioning over the year.…”
Section: Changes In Child Functioningmentioning
confidence: 60%
“…A corresponding developmental pattern has been demonstrated in a similarly designed follow-up study of former EMR-children (Svendsen, 1982). * Several studies have demonstrated IQ gains in mentally retarded persons who have been removed from a traumatic and an unstimulating environment (Clarke and Clarke, 1954;Clarke et aL, 1958;Skeels, 1966;Koluchova, 1972;Clarke and Clarke, 1976). In these studies the time interval between test and retest has been relatively short as compared to the present study, where IQ in childhood is compared to IQin adult age.…”
Section: Discussionmentioning
confidence: 87%